Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.6118/jmm.2017.23.1.15
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Husbands' Education Regarding Menopausal Health on Marital Satisfaction of Their Wives

Abstract: ObjectivesMarital satisfaction has an important effect on people's mental health. Due to the increasing average age and life expectancy of Iranian women, obtaining knowledge about sexual aspects of post-menopause women for partners can improve their health and quality of life. This study aimed to determine the effect of education for the husbands regarding menopause on marital satisfaction of their wives.MethodsThis randomized controlled trial was conducted on 100 women aged 45 to 55 years old and their husban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 11 publications
2
32
0
Order By: Relevance
“…Another inherent element of the postmenopausal period are the characteristic changes of psychosocial nature -in addition to health issues problems concerning family life and work start to emerge and may have a significant impact on the quality of life and health of postmenopausal women [10,11]. Self-esteem diminishes and the perception of their own femininity is altered [10,12]. Therefore, engaging in pro-health activities may significantly improve the condition of women in the postmenopausal period and reduce the intensity of experiencing climacteric syndrome symptoms [5,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another inherent element of the postmenopausal period are the characteristic changes of psychosocial nature -in addition to health issues problems concerning family life and work start to emerge and may have a significant impact on the quality of life and health of postmenopausal women [10,11]. Self-esteem diminishes and the perception of their own femininity is altered [10,12]. Therefore, engaging in pro-health activities may significantly improve the condition of women in the postmenopausal period and reduce the intensity of experiencing climacteric syndrome symptoms [5,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Investigators focused on health-enhancing behaviours and onanti-health activities. They examined the impact of a single activity and of several interacting activities on women's health [12,[16][17][18][19][20]. However, there are only few studies on understanding of the concept of health by women in the postmenopausal period, and there are not so many analyses of the whole spectrum of health behaviours undertaken by this group, which were measured by standardized questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…When men learn about the typical symptoms of this period, they tend to adopt assertive attitudes toward their wives, such as listening, caring, and giving more attention. By doing this they become an important source of social support, and a positive aspect for the women's experience, who feel calmer and safer (7) .…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge produced on these theme is quite broad. In this sense, the understanding of how the changes coming from the climacteric period are intertwined with the conjugal relationship is a lacuna that must be explored (6) , since it is affirmed that the influence of this phase on the conjugal relationship is inevitable, however unique because it depends on how each couple experiences their own relationship and how adjustments are made in all the other phases of the transition (6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…Mohammadalizadeh Charandabi et al found a significant positive correlation in all domains of quality of life between postmenopausal women and their spouses (5). Studies that have partnered with husbands to promote the health status of postmenopausal women, aiming at raising knowledge about menopause and its changes in quality of life (6) and perceived social support (7) and marital and sexual counseling (8,9). Few studies have been conducted on the effect of counseling on the life style of postmenopausal women; In previous studies on improving lifestyle postmenopausal women, studies did not pay attention to the importance of the dependence of the lifestyle of these women and their spouses, which we have been focusing on in this study, which can be a reflection of the novelty of this study.…”
Section: Introductionmentioning
confidence: 99%